The Impact of the Electronic Resources in Portuguese Academic Libraries: Results of a Qualitative Survey - Melo, Luiza (2012)
In the last 10 years there have been big changes in the Portuguese academic libraries services as in other academic libraries over the world. These changes include the adoption of automatic catalogues and the electronic access to bibliographic data bases and scientific journals in full text. Nowadays physical and digital sources are together. Professors, students and researchers are able to access simultaneous to a great amount of quality information pay and open access. The Portuguese Government has been investing to improve the access to the production of knowledge so as to develop the country. It is important to know the return on the investments in university libraries. The purpose of this paper is to identify the impact of the electronic sources in the Portuguese academic libraries. This paper describes an ongoing project to assess: The use of electronic scientific information and the correlation to the scientific production of the Portuguese academic community according to standard performance measures indicators and bibliometrics data. The economic value of these library services. In order to estimate in monetary terms the value of these services for end-users we use the contingent valuation method (CVM). This study reports the results of a qualitative e-survey of academic community.